103k views
5 votes
Solving systems of equations by elimination

Solving systems of equations by elimination-example-1
User Katrin
by
5.4k points

2 Answers

3 votes

x = -1 and y = -2

Explanation:

use elimination or subatitution method

User GibsonFX
by
5.1k points
5 votes

Answer:


\boxed{x = -1~~and~~ y =-2}

Explanation:

-6x + y = 4

6x - 2y = -2 +

-y = 2

y = -2

.

Substitute the value of y to the one of equations

6x - 2y = -2

6x -2(-2) = -2

6x + 4 = -2

6x = -2 - 4

6x = -6


x = (-6)/(6)

x = -1

User Peter Moresi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.